Unique transcriptome signatures and GM-CSF expression in lymphocytes from patients with spondyloarthritis - Hussein Al‐Mossawi; L. Chen; Hai Fang; Anne J. Ridley; Jelle de Wit; Nicole Yager; Ariane Hammitzsch; Irina Pulyakhina; Benjamin P. Fairfax; Davide Simone; Yao Yi; Soham Bandyopadhyay; et al. (2017)
Spondyloarthritis encompasses a group of common inflammatory diseases thought to be driven by IL-17A-secreting type-17 lymphocytes. Here we show increased numbers of GM-CSF-producing CD4 and CD8 lymphocytes in the blood and joints of patients with spondyloarthritis, and increased numbers of IL-17A+GM-CSF+ double-producing CD4, CD8, γδ and NK cells. GM-CSF production in CD4 T cells occurs both independently and in combination with classical Th1 and Th17 cytokines. Type 3 innate lymphoid cells producing predominantly GM-CSF are expanded in synovial tissues from patients with spondyloarthritis. GM-CSF+CD4+ cells, isolated using a triple cytokine capture approach, have a specific transcriptional signature. Both GM-CSF+ and IL-17A+GM-CSF+ double-producing CD4 T cells express increased levels of GPR65, a proton-sensing receptor associated with spondyloarthritis in genome-wide association studies and pathogenicity in murine inflammatory disease models. Silencing GPR65 in primary CD4 T cells reduces GM-CSF production. GM-CSF and GPR65 may thus serve as targets for therapeutic intervention of spondyloarthritis.